(untitled) (Journal of Libya for geographical studies, 2026)
This study aimed to analyze the temporal trends in the production of millet and sorghum in North Kordofan State during the period 2005–2021, to assess differences among the various localities, and to determine the state’s contribution to national production. The study was based on official data on crop production and cultivated areas obtained from the Ministry of Agriculture of North Kordofan State, national production data from the Food and Agriculture Organization of the United Nations (FAOSTAT), in addition to rainfall data derived from the CHIRPS dataset. The Mann–Kendall and Theil–Sen tests were applied, alongside linear regression analysis, to estimate trends and their statistical significance. The results indicated that production fluctuates from year to year, with an overall increasing trend, particularly for millet, which exhibited an increase rate of approximately 605 tons per hectare per year, and this increase was statistically significant. In contrast, sorghum production increased by about 263 tons per hectare per year, but this trend was not statistically significant. The year 2015 was exceptional, recording the highest production levels and contribution to national output despite relatively low rainfall (134 mm). Millet showed a weaker correlation with rainfall, as its production thrived in the localities of Jabra Al-Sheikh, Bara, and Sodari, compared to sorghum, which is more prevalent in the southern localities of Um Rawaba, Al-Rahad, and Sheikan, where rainfall is relatively more stable. The study recommended several measures, including the establishment of an integrated and accessible database to support evidence-based decision-making, and conducting a detailed investigation into the factors that contributed to the production success in 2015, with the aim of transforming these factors into a sustainable managerial and technical model.